Antibiotic removal and antibiotic resistance genes fate by regulating bioelectrochemical characteristics in microbial fuel cells. (March 2022) - Yang, Xiao-Li; Wang, Qi; Li, Tao; Xu, Han; Song, Hai-Liang
Graphical abstract: Highlights: Current intensity contributed more to antibiotics removal than anode potential. Low-concentration SMX promoted MFC performance while high concentration suppressed. Electrochemical characteristics don't affect SMX's degradation pathways. Weak current intensity decreased specific ARGs' abundance but stronger increased. High concentration of SMX made the anode potential tend to be close. Abstract: Antibiotics removal and ARGs control in microbial fuel cell (MFC) has received extensive attention. In particular, the critical role of bioelectrochemical characteristics deserves further study. Bioelectrochemical characteristics significantly affected sulfamethoxazole (SMX) removal and ARGs fate, in which the current intensity played a more critical role than anode potential. High-concentration SMX (2 mg/L and 10 mg/L) facilitated the anode potential tend to be close, and thus, the strengthening effect of current on the system was highlighted. However, the SMX degradation pathway under different bioelectrochemical characteristics was not affected. Furthermore, the higher current intensity was preferable to antibiotic removal, but unfavorable for ARGs control might be due to the oxidative stress on microorganisms. Low-concentration SMX (0.5 mg/L) contributed to improving higher electricity generation because of Geobacter enrichement. This study suggested that appropriate bioelectrochemical characteristics regulation in MFCs was essential in removing antibiotics and controlling ARGs.